2003
DOI: 10.1046/j.1365-277x.2003.00447.x
|View full text |Cite
|
Sign up to set email alerts
|

Food prepared in iron cooking pots as an intervention for reducing iron deficiency anaemia in developing countries: a systematic review

Abstract: The introduction of iron pots or improving their use in communities in developing countries for the preparation of food maybe a promising innovative intervention for reducing iron deficiency and iron deficiency anaemia. Further research is required to monitor the use and effectiveness of this intervention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
40
0
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(42 citation statements)
references
References 13 publications
0
40
0
2
Order By: Relevance
“…By 400 BCE iron largely replaced bronze and ceramic as the principle material for cooking vessels (Wells, 1984). Cooking in iron pots results in some iron uptake in the food, particularly when cooking dairy products (Kröger‐Ohlsen et al, 2002; Geerligs et al, 2003; Charles et al, 2011; Adeniyi and Ajayi, 2013; Kulkarni et al, 2013). As milk begins to sour, lactic acid bacteria can accidently or purposefully be added to the mixture to begin the fermentation process (Kunji et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…By 400 BCE iron largely replaced bronze and ceramic as the principle material for cooking vessels (Wells, 1984). Cooking in iron pots results in some iron uptake in the food, particularly when cooking dairy products (Kröger‐Ohlsen et al, 2002; Geerligs et al, 2003; Charles et al, 2011; Adeniyi and Ajayi, 2013; Kulkarni et al, 2013). As milk begins to sour, lactic acid bacteria can accidently or purposefully be added to the mixture to begin the fermentation process (Kunji et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…Beginning in the 1980s, formative research was conducted suggesting that iron cookware not only increased the iron content of food, but that this iron was bioavailable [13][14][15]. Since then, several randomized community trials have been conducted in Brazil and Africa, with varying results [10,[16][17][18]. The results of a systematic review of these early studies reveal that although the use of iron cooking vessels should theoretically be effective, cost, weight, lack of familiarity, alteration of food colour and taste, and/or some other culturally-specific concerns limit the value of this supplementation technique in practice [18].…”
Section: Discussionmentioning
confidence: 99%
“…Since then, several randomized community trials have been conducted in Brazil and Africa, with varying results [10,[16][17][18]. The results of a systematic review of these early studies reveal that although the use of iron cooking vessels should theoretically be effective, cost, weight, lack of familiarity, alteration of food colour and taste, and/or some other culturally-specific concerns limit the value of this supplementation technique in practice [18]. The iron ingot appears to overcome such concerns: it is inexpensive, (approximately $1.50 USD and probably has a life-span of more than five years, compared to monthly iron supplements that cost $2-4 USD per person); light-weight; can be used in any cooking pots regardless of construction material; the ingot does not alter the colour and taste of food as the ingot can be removed once the food is cooked; and the appearance of the fish appeared to encourage women to use it regularly.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the Ethiopian study indicated moderate height and weight gains in children assigned to treatment groups (Adish et al 1999). A more recent study conducted in Malawi verifies this research, noting a reduction in iron deficiency among children and increased hemoglobin levels in adults living under malarial endemic conditions (Geerligs et al 2003a(Geerligs et al , 2003b.…”
Section: The Use Of Adventitious Iron Sourcesmentioning
confidence: 58%